2022
DOI: 10.1002/fee.2498
|View full text |Cite
|
Sign up to set email alerts
|

Trade‐offs between utility‐scale solar development and ungulates on western rangelands

Abstract: Utility-scale solar energy (USSE) has become an efficient and cost-effective form of renewable energy, with an expanding footprint into rangelands that provide important habitat for many wild ungulate populations. Using global positioning system data collected before and after construction, we documented the potential impacts of USSE on pronghorn (Antilocapra americana), including direct habitat loss, indirect habitat loss, and barrier effects to both resident and migratory population segments. Our case study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…However, mortality of volant species due to direct impacts with solar energy infrastructure has been observed . Large mammals could lose access to all or portions of their home range and have migratory pathways disrupted, and are thus more likely to experience adverse effects from solar development. There may even be species that benefit from solar development and make use of these novel spaces to avoid predation or access previously unavailable resources .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, mortality of volant species due to direct impacts with solar energy infrastructure has been observed . Large mammals could lose access to all or portions of their home range and have migratory pathways disrupted, and are thus more likely to experience adverse effects from solar development. There may even be species that benefit from solar development and make use of these novel spaces to avoid predation or access previously unavailable resources .…”
Section: Resultsmentioning
confidence: 99%
“…Major knowledge gaps remain in our understanding of the relationship between solar energy infrastructure and wildlife. ,, To date, empirical research has documented direct negative impacts on biodiversity for plants and animals within large, ground-mounted facility footprints during the construction and operation of PV and concentrating solar power facilities. , Other studies have reported avian richness in large, ground-mounted solar facilities to be comparable to that of active pasture/cropland, but less than that of abandoned cropland, as well as lower species density and richness inside of large, ground-mounted solar facilities compared to that of facility boundary zones and unaltered controls. Beyond these studies, there is little data regarding other topics such as solar infrastructure’s influence on species ranges, behavior, occupancy/density, and, critically, movement. One study describes negative impacts of solar development on ungulates, including barrier effects on both resident and migratory populations as well as direct and indirect habitat loss, but more data are needed to characterize the relationship between solar energy infrastructure and animal movement.…”
Section: Introductionmentioning
confidence: 99%
“…Pronghorn consistently avoid roads, with larger traffic volumes associated with higher risk perception, and groups with fawns exhibit even greater risk perception and avoidance behavior (Gavin and Komers 2006, Fleishman et al 2017, Reinking et al 2019, Lambert et al 2022, Robb et al 2022). Energy development in the Intermountain West has resulted in significant loss of high‐quality habitat, causing changes in pronghorn behavior and resource selection patterns (Beckmann et al 2012, Reinking et al 2019, Smith et al 2020, Milligan et al 2021, Sawyer et al 2022). Beckmann et al (2016) discuss the difficulties in understanding broader consequences of energy development on pronghorn habitat and fitness.…”
Section: Resultsmentioning
confidence: 99%
“…The question of how the construction of USSE impacts long‐term diversity is ripe for investigation. Of special interest would be if the construction and operation of the ISEGS facility significantly alters (1) hydrological patterns supporting intermittent and ephemeral washes that are preferred substrates for Mojave milkweed germination and establishment (Grippo et al, 2015), (2) patterns of herbivory owing to fencing that may impact animal movement within and outside the facility's footprint (Grodsky et al, 2020; Sawyer et al, 2022), and (3) habitat fragmentation. All effects individually or combined may lead to reduced genetic variation and loss of local genetic structure in plant populations (Young et al, 1996).…”
Section: Discussionmentioning
confidence: 99%